Agro-industrial residues from Amazonian fruits: bioactive composition, bioaccessibility and potential use as a prebiotic - Silva, Anna Paula de Souza (2023)
The intense global generation of waste and by-products resulting from agro-industrial activities indicates the need for studies to reuse these materials. This work aimed to determine the nutritional and bioactive composition, and prebiotic potential of by-products (meals) from the processing of açaí (Euterpe oleracea Mart) and inajá (Maximiliana maripa Aubl Drude) as natural sources of nutrients and compounds with antioxidant and anti-inflammatory activities. Açaí and inajá meals were prevenient from the processing of the fruits for oil extraction. Initially, the proximate composition and the mineral profile of the raw materials were determined, followed by the assessment of the prebiotic potential using probiotic bacteria (Lacticaseibacillus rhamnosus and Bifidobacterium animalis subsp. lactis). Subsequently, the extracts of the meals were subjected to in vitro gastrointestinal digestion, thus obtaining the bioaccessible fraction (BF) of each one, which was analyzed by LC-ESI-QTOF-MS/MS for identifying bioactive molecules. The non-digested extracts (NDE) and their respective BF were evaluated in vitro for the total phenolic content (TPC) and scavenging capacity against the radicals peroxyl, superoxide anion, and hypochlorous acid. The anti-inflammatory activity of NDE and BF was determined by the inhibition of NF-B activation and TNF-α. The NDE and BF of açaí and inajá were also evaluated for acute toxicity in Galleria mellonella. In the proximate composition, the dietary fiber content was 80.11 ± 2.55 and 62.16 ± 3.39% for açaí and inajá, respectively). Both by-products showed a diversified mineral profile and, in general, with higher levels compared to the pulps of the respective fruits. Mg, K and S are among the elements present in higher concentrations. For the prebiotic potential, both meals increased the viability of the bacteria after 24 hours of fermentation in culture media containing the by-products, with emphasis on the result of the inajá meal for L. rhamnosus (8.3 ± 0.1 log CFU/mL). Phenolic acids, isoorientin, and vitexin, were identified in açaí BF, while caffeic acid hexoside, citric acid, glabridin, and eriodictyol 7-O-glucoside were identified in inajá BF, attesting that these compounds may be responsible for the assessed biological activities. For TPC, no statistical difference was observed between NDE and BF of the same by-product, but a significant difference was observed between NDE and BF of different by-products. The peroxyl radical scavenging capacity of açaí NDE decreased about 2.3 times after digestion, while for inajá there was no statistical difference, with inajá BF being 1.42 times more efficient compared to açaí BF. The NDE and BF of the by-products also were capable of scavenging hypochlorous acid. For anti-inflammatory activity, macrophages treated with 100 μg/mL of NDE or BF from açaí reduced NF-B activation by 80 and 85%, against 33 and 96% of NDE and BF from inajá, respectively. TNF-α levels were reduced by 70 and 81% for açaí NDE and BF, respectively, and by 93% for inajá BF. Finally, the evaluation of in vivo toxicity indicated toxic effects in G. mellonella larvae treated with NDE of açaí (0.1 g/kg) and inajá (4 g/kg). However, the BF of both by-products did not present toxicity. Therefore, the results of this work indicate that açaí and inajá meals have the potential for industrial reuse as possible sources of fibers and minerals with potential prebiotic activity; as well as raw materials for the extraction of natural compounds with antioxidant and anti-inflammatory action.